MEDIA MASSA DAN CYBER CRIME DI ERA SOCIETY 5.0: Tinjauan Multidisipliner - Muhamad Bisri Mustofa; Evin Luthfiah Dwiandrini; Indriani Agustin; M. Afief Esyarito; Mutiara Anggraeni; Siti Wuryan (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2022)
The mass media in the era of society 5.0 is the main means of disseminating messages and information to the wider community. The era of society 5.0 and the birth of new media has made people's daily lives easier. Currently, the mass media has a dual role, namely as a means of sharing messages in the flow of communication and also acting as an agent of change for the community. Many people's expectations of the role of mass media as agents of change for the wider community to become even better turned out to have a myriad of challenges. Because basically the mass media has a flexible nature. Mass media as a means of disseminating information and messages to the wider community is in line with the realities of life, every new change of course has new risks that follow. The rapid development of mass media also brings the rapid development of cyber crime in human life. And here is a new challenge that must be faced by every party in the era of society 5.0. Reflecting on the case above, the research in this journal focuses on discussing the challenges that must be faced by each party involved in society 5.0 in the era of cyber crime that attacks all aspects of life. This research uses an explanatory method based on literature study in which all data are obtained from books, journals, articles and internet media. This study aims to see and find out to what extent the parties involved in society 5.0 face cyber crime, especially the mass media. The theory used in this study is social learning theory to discuss the reasons for the existence of cyber crime, then use and gratification theory to see the extent to which society is affected by mass media in society 5.0 and finally media ecology theory to see how the role of mass media is in dealing with cybercrime.